Simulation of the high-octane alkylates manufacturing considering the process unsteadiness; Petroleum Science and Technology; Vol. 36, № 7 - Dolganova I. O. Irena Olegovna; Burykhina E. S. Elizaveta Sergeevna; Ivashkina E. N. Elena Nikolaevna; Bekker A. V. Aleksandr Viktorovich (2018, 2018)
Title screen